PROFITABILITY, LIQUIDITY, COMPANY SIZE TO DIVIDEND POLICY - halimatus sadiyah; Aditya Hermawan (Jurnal Ekonomi, 2023)
Intense competition between companies encourages every company to always want to strengthen their financial position. Increasing capital is one way for companies to continue to survive in the current global economic situation. Therefore, the company seeks to attract many investors in the company's financing activities. The purpose of this study was to determine the effect of profitability, liquidity, and company size on dividend policy. This study uses a causal-acsesitive method, which is research that aims to determine the influence between variables. The research sample consisted of business groups registered with IDX in 2019-2021, using the purposive sampling method. Although there has been a lot of research done on the company's dividend policy, the results are mixed.